A new species of Ceropegia (Asclepiadoideae, Apocynaceae) from eastern Thailand - Kidyoo, Manit (Phytotaxa, 2018)
Ceropegia boonjarasii Kidyoo, a new species from eastern Thailand is here described, illustrated and compared morphologically and ecologically to C. sootepensis Craib and C. laotica Rodda & Meve, its putative close relatives. These three species display clear differences in habitat choice, hairiness of leaf surface and corolla lobes, and in the shape of interstaminal corona segments.